Hemangioma Verukosa - Rinandari, Ummi; Yustin Ellista Sari, Endra (PT Dexa Medica, 2020)
Verrucous hemangioma (VH) is a localized verrucous venous malformation comprising a capillary or cavernous hemangioma with proliferation reactions such as epidermal hyperkeratosis, acanthosis or papillomatosis also vascular proliferation and widening in the dermis to subcutaneous tissue. This disorder is usually found in the lower extremities and unilateral. It is often misdiagnosed as venous or lymphatic malformations. An 11 year-old boy presented with rough patches and blackish-red lumps on the right leg since birth. Four months prior, the lesion bled after being hit by ball and became rougher, thickened and darker thereafter. He was initially diagnosed with hemangioma and cryotherapy was performed, but there was no improvement after 6 cryotherapy treatment. A diagnosis of VH should be considered in the presence of erythematous papules, nodules, and plaques, especially those that are hyperkeratotic, present at birth, located at the lower extremities, and progressively enlarge after trauma or infection. Based on patient history, physical examination and laboratory results, the patient was diagnosed with VH. Excision surgery is the gold standard of VH management. The excision of the lesion must be deep and wide with a margin of 1 cm, to minimize recurrence. Treatment consists of combination of clobetasol propionate 0.05% and salicylic acid 5% ointment before excision was performed.